Lima Tahap Penguasaan Ilmu Nahu dalam Kalangan Guru- Guru Sijil Tinggi Agama Malaysia (STAM) - Hazrul Affendi, Mohmad Razali (Center for Communication Technology And Human Development (UniMAP), 2018)
Link to publisher's homepage at http://johdec.unimap.edu.my